Study Of General Health Among Tehran University Of Medical Sciences Hospital's Administrators - Mahmood Biglar; Yeganeh Hayati; Hojjat Rahmani; Zeynab Rajabnezhad; Hossein Dargahi (Tehran University of Medical Sciences, 2014)
Background and Aim: One of the most important factors to present successful managers is general health. If managers have not highly general health, then they will encounter many problems. Therefore, this research is aimed to induce the general health among Tehran University of Medical Sciences hospitals' administrators.  Materials and Methods: A cross-sectional, deceptive and analytical study was conducted among 25 Tehran University of Medical Sciences hospitals administrators in Tehran, Iran. The research tool was general health questionnaire developed by Goldberg and Hillier to assess the administrators general health and its demographic details. Data was analyzed by SPSS software and using analytic statistical methods. Results: The results of this study showed that the hospitals administrators had normal range of general health. Also, there was significant correlation between anxiety with physical dysfunctions, and depression with physical dysfunctions, and anxiety with social functions. Conclusion: The rate of general health among TUMS hospitals administrators is higher than the other mangers compared with similar studies in Iran and out of Iran. Therefore, we suggest periodic medical examination, general health training, and consultant services to develop or maintain the general health among healthcare managers.